(untitled) (lectio difficilior, 2016)
Syriac literature in Late Antiquity is a many-voiced choir filled with women’s vocals. They appear as active parts of the liturgy and in vivid depictions of biblical women, giving a voice to Eve’s grief, Mary’s muddle, Sara’s struggle. This essay aims to shed light on the themes of suffering and death as resonated through women’s voices in selected ancient Syriac texts. It is set out to be an exemplary excursion into the rich treasury of Syriac literature with its many aspects of gender and the exposure to mortality, affliction and death.